Analisis Pelayanan Publik Menggunakan Customer Relationship Management Model - Sela Taramita; Zena Lusi (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This research is motivated by efforts to develop digital services to improve the quality of electronic government-based services at the Population and Civil Registration Service (Disdukcapil) of Palembang City. This study applies the Customer Relationship Management (CRM) model approach to 10 areas of public services available on the official website of the Palembang City Disdukcapil. The variables used in this study include commitment to information technology (IT), IT-related communication, service quality, and customer satisfaction in utilizing digital-based services. The research method used is descriptive with a quantitative approach. Data collection was carried out through a Google Form-based questionnaire, which was distributed via WhatsApp social media to the Palembang City community as respondents. The results of the study processed using SPSS showed that the data tested for validity were declared valid. The reliability test produced a Cronbach's Alpha value of 0.982, which exceeded the standard of 0.7, indicating high data consistency. Meanwhile, the results of the analysis using AMOS showed that the level of customer satisfaction in using the Disdukcapil website reached 95% for the commitment variable, 94% for the communication variable, and 95% for the service quality variable. Overall, this study shows that customer satisfaction with the digital services of the Palembang City Population and Civil Registry Office is in the good category. The results of this study are expected to provide insight and recommendations for the government in designing policies to improve the quality of electronic government services in the city of Palembang.